Color preference for shirts of selected Filipino working men in Metro Manila - Cular, Coreene Ann G.
This is a descriptive study that was conducted to determine the color preference for shirts of selected Filipino men in Metro Manila. Data were collected through a sample survey with a self-administered questionnaire. Through random sampling, a total of 80 Filipino working men, ages 23 to 40 years old, who are working in the Metro Manila area, were selected as respondents for this study. The survey was conducted from January to February 2007. The results show that white is the most preferred color for shirts by the selected respondents. The top five most preferred colors for knit shits were classified according to the following colors of the matching denim pants: a) for dark denim: white, tint of yellow, tint of blue-green, light gray, tone of yellow and flesh; b) for regular denim: white, light gray, tint of blue green, dark gray, tone of blue and gray; c) for faded denim: white, black, gray, shade of red, brown, red and light gray. In the same manner, the following are the top five most preferred colors for woven button down shirt when paired with slacks: a) for black slacks: white, tint of yellow, tint of blue-green, light gray, and flesh; b) for gray slacks: white, tint of blue green, gray, light gray, and tint of blue; and c) for khaki slacks: white, black, cream, gray, light gray, and dark brown. The data indicated that the respondents prefer neutral colors for their shirts in matching with pants. The study also determined the influencing factors that affect the respondents' color preference for shirts to match pant; these are the following: Occasion, Personality, Weather, Skin color, and personal mood.